Analisis dosis pada pemeriksaan computer tomography (ct) scan kepala dan prosentase resiko kanker di RSUD dr. Saiful Anwar Malang - Anam, Khoirul (Maliki Interdisciplinary Journal, 2024)
CT iScan ihas ia ihigher idose ithan iother iradiology itools. iThe iparameters ithat iaffect ithe iradiation idose ireceived iby ithe ipatient iinclude ithe iexposure ifactor, inamely ithe iX-ray itube ivoltage iand ithe itube icurrent. iTube ivoltage iand icurrent iare iX-ray igenerator iparameters, iso ithey iaffect ithe iintensity iof iradiation ireceived iby ithe ipatient. iThe ieffective idose ireceived iby ithe ipatient imust inot iexceed ithe istandards iset iboth inationally iand iinternationally. iNationally, ithe idose ireceived iby ipatients iis iregulated iin ithe iRegulation iof ithe iHead iof iBapeten iconcerning ithe iDiagnostic iReference iLevel i(DRL). iMeanwhile, iinternationally iit iis iregulated iin ithe iInternational iCommission ion iRadiological iProtection i(ICRP), iespecially iin iICRP iPublication i102 inamely iManaging iPatient iDose iin iMulti-Detector iComputer iTomography i(MDCT). iIf ithe idose ireceived iis igreater ithan ithe istandard iset, iit iwill icause idamage ito ibody itissue icells iand igenetic idamage iin ithe iform iof imutations iin ireproductive icells.